ANALISIS PENGAKUAN PENDAPATAN PERUSAHAAN KONSTRUKSI PROYEK BENDUNGAN MARANGKAYU PADA PT.LUHRIBU NAGA JAYA SAMARINDA - Camelia Verahastuti, Aris Farmuzi, Elfreda Aplonia Lau (EKONOMIA, 2015)
Construction services is a sector that will continue to grow as long as the construction is still running. Currently, development in Indonesia is increasing, whether the construction of buildings, factories, public facilities and on.Therefore, one element of which is closely related to the size of the profit generating companies is revenue. Revenue should be measured at the fair and it must be ensured in accordance with the revenue recognition and the principle - the principle of Statement of Financial Accounting Standards (SFAS) No. 34 PT. Luhribu Naga Jaya method for the physical Progress, revenue recognition method used by the company is not in accordance with the applicable financial accounting standards that SFAS No. 34 on construction services Basic theory used is the Accounting Theory by means of a comparative analysis that compares the company's financial statements with the financial statements in accordance with Statement of Financial Accounting Standards (SFAS) No. 34 on the Recognition Revenue Construction Company